The promotion of active aging through older adult education in the context of population aging - Kexin Zhang; Kexin Zhang; Chengxia Kan; Chengxia Kan; Youhong Luo; Youhong Luo; Hongwei Song; Hongwei Song; Zhenghui Tian; Wenli Ding; Wenli Ding; Linfei Xu; et al. (Frontiers Media S.A., 2022)
We have entered an era of population aging, and many public health problems associated with aging are becoming more serious. Older adults have earlier onset of chronic diseases and suffer more disability. Therefore, it is extremely important to promote active aging and enhance health literacy. These involves full consideration of the need for education and the provision of solutions to problems associated with aging. The development of OAE is an important measure for implementing the strategy of active aging, and curriculum construction is a fundamental component of achieving OAE. Various subjective and objective factors have limited the development of OAE. To overcome these difficulties and ensure both active and healthy aging, the requirements for active aging should be implemented, the limitations of current OAE should be addressed, system integration should be increased, and the curriculum system should be improved. These approaches will help to achieve the goal of active aging. This paper discusses OAE from the perspective of active aging, based on the promotion of health literacy and provides suggestions to protect physical and mental health among older adults, while promoting their social participation. The provision of various social guarantees for normal life in older adults is a new educational concept.